News shocks and labour market dynamics in matching models. (August 2016) - Theodoridis, Konstantinos; Zanetti, Francesco
Abstract: We enrich a baseline real business cycle (RBC) model with search and matching frictions on the labour market and real frictions that are helpful in accounting for the response of macroeconomic aggregates to shocks. The analysis allows shocks to have an unanticipated and a news (i.e., anticipated) component. The Bayesian estimation of the model reveals that the model that includes news shocks on macroeconomic aggregates produces a remarkable fit of the data. News shocks in stationary and non‐stationary TFP, investment‐specific productivity and preference shocks significantly affect labour market variables and explain a sizeable fraction of macroeconomic fluctuations at medium‐ and long‐run horizons. Historically, news shocks have played a relevant role for output, but they have had a limited influence on unemployment.